2014
DOI: 10.18553/jmcp.2014.20.8.800
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Early Disease-Modifying Drug Adherence Measure to Predict Future Adherence in Patients with Multiple Sclerosis

Abstract: BACKGROUND: Patients with multiple sclerosis (MS) who are adherent to their treatment regimens are less likely to experience relapses and the cost associated with relapse. Pharmacists whose practice involves these specialty pharmaceuticals used to treat MS are striving for ways to improve outcomes by achieving treatment adherence in their patients. Specialty pharmacies have reported higher adherence rates than traditional pharmacies, which may translate to improved outcomes. Identifying patients who warrant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…We only examined adherence in the first year of therapy, but measured outcomes over a longer term. This was based on the work demonstrating that models that included levels of early adherence measured over a 1‐year period were predictive of adherence over the subsequent 1‐year period . We made the assumption that this predictability would be constant over a longer period of time, although we were not able to test this assumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We only examined adherence in the first year of therapy, but measured outcomes over a longer term. This was based on the work demonstrating that models that included levels of early adherence measured over a 1‐year period were predictive of adherence over the subsequent 1‐year period . We made the assumption that this predictability would be constant over a longer period of time, although we were not able to test this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Also, discontinuations due to adverse effects have been shown to typically occur within the first year of therapy . Finally, early adherence levels have been shown to predict future adherence in MS patients . An MS‐specific hospitalization was defined as an admission with a primary diagnosis recorded as MS (ICD‐9 or 10: 340 or G35).…”
Section: Methodsmentioning
confidence: 99%
“… 22 Second, this method facilitated a degree of separation between the exposure (adherence) and outcome (disability accumulation). Finally, previous studies have shown that early adherence after drug initiation is predictive of later adherence in some chronic conditions, including MS. 6–8 One recent study from an American-managed care program database found that adherence over the 1-year period immediately following IMD initiation predicted adherence over the subsequent year. 6 Similarly, adherence to statins during the first 4 months after therapy initiation was shown to predict adherence over the subsequent year in a large North American population.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Adherence levels early in treatment predict future adherence patterns. 6–8 In general, poor medication adherence is associated with poorer health-related outcomes, including higher risk of morbidity and mortality, increased health services utilisation and increased healthcare costs. 9–11 In MS, poor adherence to the IMDs is associated with decreased quality of life, higher relapse rates and higher medical costs.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Some studies have measured persistence and linked behavior to relapse outcomes; [21][22][23][24][25][26][27][28] however, few have focused specifically on natalizumab, [13][14][15]24,29 and of those studies, none have focused on natalizumab treatment patterns and the resulting impact on relapse-related outcomes in a large U.S. commercially insured population.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%